PENGARUH BRAND AMBASSADOR, BRAND IMAGE, BRAND TRUST TERHADAP MINAT BELI: SEPATU SPECS - Dispar, Kevin Arigi; Anggarawati, Sularsih (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This article aims to examine the influence of brand ambassador, brand image and brand trust on purchase intention. As many as 238 respondents used non-probability techniques in purposive sampling as a sampling technique. This research uses regression analysis tools. The research results show that brand ambassador does not have a significant influence on purchase intention, brand image has a significant influence on purchase intention, then brand trust also has a significant influence on purchase intention in purchasing SPECS sports shoes.